2009
DOI: 10.1002/ptr.2982
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of 3′‐deoxy‐4‐O‐methylepisappanol from Caesalpinia sappan against glutamate‐induced neurotoxicity in primary cultured rat cortical cells

Abstract: To examine the neuroprotective effects of Caesalpinia sappan L., we tested its protection against the glutamate-induced neurotoxicity in primary cortical cultured neurons. We found that an aqueous extract of this medicinal plant exhibited significant protection against glutamate-induced toxicity in primary cultured rat cortical cells. In order to clarify the neuroprotective mechanism(s) of this observed effect, isolation was performed to seek and identify active fractions and components. By such fractionation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Several studies have shown that CS has antimicrobial and bactericidal activity [8] and antiallergic [9], neuroprotective [10], and hypoglycaemic effects [11]. Others found that extract from CS can be used for treating ascites, tumour, leukaemia [12], and arteriosclerosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CS has antimicrobial and bactericidal activity [8] and antiallergic [9], neuroprotective [10], and hypoglycaemic effects [11]. Others found that extract from CS can be used for treating ascites, tumour, leukaemia [12], and arteriosclerosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…9 Toxicodendron vernicifluum (Stokes) F.A. 47 From the same plant, littorachalcone (CS 3.34) doubled the neuritogenic effects of 2 ng/mL of NGF against PC12 cells. Br.)…”
Section: Chapter 3 Phenolicsmentioning
confidence: 99%
“…Other compounds, such as sappanchalcone 19 and 3'-deoxy-4- O -methylepisapanol ( 54 ), which were obtained from the methanol extract from barks of C. sappan , were evaluated in cortical cells of rats injured with glutamate at doses of 0.1 to 10 µM. Only compound 54 showed significant activity, attenuating the toxicity induced by glutamate with cellular viability of 50–70% [ 63 , 64 ]. Other compound isolated from C. sappan , neo-sappanone ( 55 , Figure 4 ), was evaluated for inhibition of xanthine oxidase and showed a dose-dependent inhibitory activity with IC 50 of 29.7 µM, 10-fold less potent than the positive control allopurinol (IC 50 = 2.6 µM).…”
Section: Phytochemicals and Pharmacological Aspectsmentioning
confidence: 99%